Intra-accumbens Raclopride Administration Prevents Behavioral Changes Induced by Intermittent Access to Sucrose Solution - Suárez-Ortiz, Josué O.; Cortés-Salazar, Felipe; Malagón-Carrillo, Ariadna L.; López-Alonso, Verónica E.; Mancilla-Díaz, Juan M.; Tejas-Juárez, Juan G.; Escartín-Pérez, Rodrigo E. (Frontiers in Neuroscience, 2018)
Overeating is one of the most relevant clinical features in Binge Eating Disorder and in some obesity patients. According to several studies, alterations in the mesolimbic dopaminergic transmission produced by non-homeostatic feeding behavior may be associated with changes in the reward system similar to those produced by drugs of abuse. Although it is known that binge-eating is related with changes in dopaminergic transmission mediated by D2 receptors in the nucleus accumbens shell (NAcS), it has not been determined whether these receptors may be a potential target for the treatment of eating pathology with binge-eating. Accordingly, the aim of the present study was to evaluate whether sugar bingeing induced by intermittent access to a sucrose solution produced changes in the structure of feeding behavior and whether blocking D2 receptors prevented these changes. We used the intermittent access model to a 10% sucrose solution (2 h/day for 4 weeks) to induce sugar bingeing in Sprague Dawley female rats. Experimental subjects consumed in a 2-hour period more than 50% of the caloric intake consumed by the subjects with ad-lib access to the sweetened solution without any increase in body weight or fat accumulation. Furthermore, we evaluated whether sugar bingeing was associated to the estrous cycle and we did not find differences in caloric intake (estrous vs diestrus). Subsequently, we characterized the structure of feeding behavior (microstructural analysis) and the motivation for palatable food (breakpoints) of the subjects with sugar bingeing and found that feeding episodes had short latencies, high frequencies, as well as short durations and inter-episode intervals. The intermittent access model did not increase breakpoints, as occurred in subjects with ad-lib access to the sucrose. Finally, we evaluated the effects of D2 receptor blockade in the NAcS, and found that raclopride (18nM) prevented the observed changes in the frequency and duration of episodes induced by intermittent access to the sucrose solution. Our results suggest that alterations in behavioral patterns associated with binge-eating behavior depend in part on the dopaminergic transmission in the NAcS and that the antagonism of D2 receptors may be a therapeutic tool for feeding pathology with binge-eating.